Assessing taxpayers’ satisfaction with tax administration e-services - Lidija Hauptman; Nika Vetrih; Alenka Kavkler (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
As tax administrations worldwide modernize through digital technologies, it has become increasingly important to understand taxpayers’ satisfaction with these services. This research aims to estimate the relationships between satisfaction with tax administration e-services and factors such as trust, service quality, age, and gender, addressing a noted gap in the existing literature. Using the questionnaire distributed among taxpayers in Slovenia, four hypotheses were tested. Next to descriptive methods, Pearson correlation analysis, T-tests, and Mann-Whitney U-tests were used. The findings reveal a positive correlation between e-service quality and trust, as well as sustainability, but lower satisfaction with tax administration e-services among the younger generation. Gender differences do not exist, as male and female taxpayers are perceived to be equally satisfied with the e-service. The results suggest that improving tax information’s usability, clarity, and security increases taxpayers’ confidence and satisfaction. Quality information does not cause confusion and distrust. From the taxpayers’ perspective, it is essential to ensure accessible, easy-to-understand information and implement quick feedback mechanisms to enhance clarity and strengthen taxpayers’ trust.